PENGARUH PERBEDAAN WAKTU PENANGKAPAN ANTARA PAGI DAN MALAM HARI TERHADAP HASIL TANGKAPAN IKAN MENGGUNAKAN ALAT TANGKAP JARING LINGKAR (MINI PURSE SEINE): The Effect Of Differences In Catching Time Between Morning and Evening On Fish Catches Using Circle Netting Equipment (Mini Purse Seine) - Ardiana Rusianto; Raismin Kotta; Aryani Rahmawati; Denianto Yoga Sativa (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2023)
A purse seine is a tool (gear) used to catch pelagic fish that form schools. The aims of this study were 1) to determine the effect of different catches using Mini Purse Seine fishing gear in the morning and evening, 2) to find out the most effective time of catching fish using Mini Purse Seine fishing gear, and 3) To find out composition of the catch and the type of fish caught in the Mini purse seine fishing gear in the morning and at night. The method used in this study was an experimental method with a completely randomized design. This research was conducted in the waters of Ganggelang Village, Gangga District, North Lombok Regency. The results showed that there was no effect of differences in fish catches using Mini purse seine fishing gear in the morning and at night, but there were differences in the composition of fish catches in the morning and at night. The catch of fish at night is more: 1,028 fish while in the morning around: 620 fish, so the effective time for catching fish using the Mini Purse Seine fishing gear is at night. The most dominant type of fish caught in the morning was 175 mackerel and 295 julung-julung fish at night